2000
DOI: 10.1097/00007632-200007150-00016
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of One-Level Posterior Lumbar Interbody Fusion for Spondylolisthesis and Postoperative Intervertebral Disc Degeneration Adjacent to the Fusion

Abstract: There is no evidence from the results that postoperative narrowing of the adjacent disc and preoperative narrowing of the L5-S1 disc affects the clinical outcome of L4-L5 PLIF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(104 citation statements)
references
References 20 publications
4
96
1
3
Order By: Relevance
“…Survivorship analysis by Ghiselli et al [9] has shown that the 10-year survival rate of the L5-S1 segment after isolated L4-5 fusion was 90%. Miyakoshi et al [16] suggested that the L5-S1 segment does not have to be routinely included in fusion, even in the presence of degenerative changes, because the clinical outcome of L4-L5 fusion is not affected by narrowing of the L5-S1 disc. We also found that the incidence of distal ASD was much lower than that of proximal ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Survivorship analysis by Ghiselli et al [9] has shown that the 10-year survival rate of the L5-S1 segment after isolated L4-5 fusion was 90%. Miyakoshi et al [16] suggested that the L5-S1 segment does not have to be routinely included in fusion, even in the presence of degenerative changes, because the clinical outcome of L4-L5 fusion is not affected by narrowing of the L5-S1 disc. We also found that the incidence of distal ASD was much lower than that of proximal ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the clinical implication of a radiologically demonstrated ASD is uncertain. Many authors have found no correlation between radiological ASD and clinical symptoms [15,21,22,26,30,31,35,44,46].…”
Section: Introductionmentioning
confidence: 99%
“…There is a controversy regarding the risk factors involved in the development of ASD [2,11,12,22,28,40,41,47,[57][58][59]. Non-rigid, dynamic or flexible instrumentations for lumbar spine have been developed to reduce ASD [17,18,27].…”
Section: Introductionmentioning
confidence: 99%